NEUROPROTECTIVE EFFECT OF ABELMOSCHUS ESCULENTUS ON CHRONIC STRESS AND EVALUATION OF LOSS OF MEMORY, ADAPTOGENIC EFFECT - CHENOLY, SHABINA KOMATH; C, SHANKARAPPA; PINNELLI, VENKATA BHARATKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Objective of this study was to determine if there was any neuroprotective effect of Abelmoschus esculentus L and its role in preventing memory loss during stressful conditions. Methods: The powder of A. esculentus L. pods was extracted with methanol and was used for evaluating anti-stress activity in experimental mice groups. The five experimental mice groups, namely, control, stress control, animals treated with extract followed by exposure to stress, animals exposed to stress followed by extract treatment, and mice groups treated with diazepam was evaluated. Biomarkers included were cortisol, brain homogenate acetylcholine esterase (AchE), superoxide dismutase (SOD), and malondialdehyde (MDA). In conjugation, working memory and reference memory were also studied in all animal groups by radial arm maze test, and results were recorded as the percentage of alteration score (PAS). Results: The concentration of stress indicators such as cortisol, MDA, and AchE activity was significantly elevated in stress control animals and associated with deficit working and reference memory. However, SOD was reduced in stressed mice and increased in treatment groups compared to the control mice. The anti-stress activity of A. esculentus L. pods was significantly correlated with higher working memory and reference memory with 1.33±0.51 and 1.17±0.40 PAS in pre-stress and post-stress treated mice groups, respectively. Conclusion: Methanolic extract of A. esculentus L. pods revealed the excellent anti-stress potential and also played a significant role in enhancing both working memory and reference memory in mice.